2019
DOI: 10.3390/cells8040302
|View full text |Cite
|
Sign up to set email alerts
|

Collagen I Promotes Adipocytogenesis in Adipose-Derived Stem Cells In Vitro

Abstract: A hallmark of ageing is the redistribution of body fat. Particularly, subcutaneous fat decreases paralleled by a decrease of skin collagen I are typical for age-related skin atrophy. In this paper, we hypothesize that collagen I may be a relevant molecule stimulating the differentiation of adipose-derived stem cells (ASCs) into adipocytes augmenting subcutaneous fat. In this context lipogenesis, adiponectin, and collagen I receptor expression were determined. Freshly isolated ASCs were characterized by stemnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Furthermore, it has been reported that hypoxia results in the ASC secretion of neovascularization growth factors such as VEGF, and therefore induces neovascularization in an ischemic environment after transplantation [33]. ASC presents in subcutaneous adipose tissue can differentiate into adipocytes [34]; it has been reported that when ASC are cultured from collagen, more lipids are produced, which is a marker of adipose differentiation [35]. Therefore, collagen impregnation could support ASC differentiation into adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that hypoxia results in the ASC secretion of neovascularization growth factors such as VEGF, and therefore induces neovascularization in an ischemic environment after transplantation [33]. ASC presents in subcutaneous adipose tissue can differentiate into adipocytes [34]; it has been reported that when ASC are cultured from collagen, more lipids are produced, which is a marker of adipose differentiation [35]. Therefore, collagen impregnation could support ASC differentiation into adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To address how ECM affects adipogenesis and adipocyte function, Type I collagen-based hydrogel can be utilized to mimic physiologically relevant adipogenic microenvironments, since it can be modified in terms of biophysical and biochemical properties [ 112 ]. Tissue culture plastic coated with type I collagen has been reported to enhance adipogenesis [ 113 ], while type VI collagen appears to restrict adipose expansion [ 114 ]. Interestingly, by blocking an attachment of integrin alpha 6 to laminin, it allowed differentiation of adipocytes due to sustained anti-adipogenic RhoA activity [ 115 ].…”
Section: Modeling Adipogenesis Via Three-dimensional (3d) Culturementioning
confidence: 99%
“…Biomaterials should provide an adequate environment for cultures cells and thereby play a crucial role in tissue engineering process. To date there are a variety of available materials for adipose tissue engineering such as gelatine [1], collagen [2], alginate [3] or combinations thereof. However, these materials cannot represent the complexity of the natural ECM and the typical organization of native tissue.…”
Section: Introductionmentioning
confidence: 99%